Parity Relationship with Pregnant Women's Knowledge About Anemia in The Sentani Health Center of Jayapura Regency - Sainafat, Adriana; Zainuddin, Fatmawati (International Conference on Sustainable Health Promotion, 2018)
Anemia in pregnant women is the iron deficiency, and blood is characterized by hemoglobin levels below average, which is <11 gr%. Pregnant women who experience anemia can increase the risk of premature birth, Low Birth Weight Babies (LBW), the risk of bleeding before and during childbirth, and can even cause maternal and fetal death. Factors that cause these deaths are 3T of whom are too old at the time of parturition (> 35 years), too easy during childbirth (<20 years) and too brittle the birth spacing is <2 years. The purpose of the research related to this problem was to find out the relationship between parity and the knowledge of pregnant women about anemia in the Sentani Health Center in Jayapura Regency. The type of research used is analytic with the cross-sectional approach. The population in this study were all pregnant women in Sentani health centers with a sample of 80 respondents using random sampling techniques. Data were analyzed using univariate frequency distribution and bivariate tables using chi-square statistical test. The results showed that the knowledge of pregnant women about Anemia at the Sentani Health Center with sufficient knowledge was 48.8% and most had more than three children (multiparous) as much as 45%. There is no relationship between parity and pregnant women 's knowledge of anemia in Sentani Health Center as evidenced by a statistical test obtained by P-value = 0.06 (p <0.05). It can be concluded that there is no relationship between the knowledge of pregnant women about anemia in the Sentani Health Center, most of them have sufficient experience. Therefore, it is recommended for all parties to further improve the promotion service especially in providing IEC about anemia during pregnancy.